Desenvolvimento de um método para determinação de ácidos orgânicos em sucos de frutas utilizando Eletroforese Capilar de Zona (ECZ) - Carvalho, José Marcos Valentim de (2010)
An electrophoretic methodology with UV detection was developed for determinations the main organic acids contained in fresh fruit juice and industrialized fruits juices produced in Sergipe/Brazil and sold in markets and supermarkets of Lagarto, Itabaiana and Aracaju. Oxalic, tartaric, citric, gallic and ascorbic (L aa) organic acids were separate and quantified in grape, orange, lemon, carambola, umbu-caja, acerola, cashew, strawberry samples of fresh juices and samples of mixed juice industrialized (mixed acerola, orange, fortified whit L aa; mixed apple, orange, tangerine and lemon; mixed orange, lemon and tangerine; guava juice and mixed apple, lemon and grape). The analyses were made employing BGE containing 100 mmol/L borate buffer pH 10.0 and 0.5 mmol/L cetyl trimethyl ammonium bromide (CTAB) as EOF-modifier, a fused silica capillary of 59 cm of length (23.7 cm effective, 75 mm of i.d.) = 214 nm. The sample injection was made in hydrodynamic mode (height 4.5 cm) for 15 s, the method was linear within 0.0040 to 0.0450 g/100mL. The calibration curves were prepared with the addition of external standard, with correlation coefficient from 0.9912 to 0.9995, the precision ranged of 1.48 to 11.46% (n= 3). The limit of detection varied from 0.0005 to 0.0155 g/100mL and the limit of quantification varied from 0.0016 to 0.0517 g/100mL. The recoveries in samples of fresh juices were 83.6 to 117.5% (n = 50) and from 83.60 to 108.7% (n=11) for the acids in fruits juices industrialized samples. The oxalic, tartaric, citric, and L aa were separated and quantified in samples of fresh juices while citric and L aa acid in samples of industrialized juices there was reduction in the concentration of 18.90%, 28.20% and 36.00% L - aa of juices of fresh acerola, orange and cashew respectively and of 100.0%, 99.40% in samples of mixed juice industrialized, mixed apple, orange, tangerine and lemon, mixed acerola, orange, fortified whit L aa respectively, was also reduction the concentration of citric acid in two samples juice industrialized 15,20% in mixed apple juice, orange, tangerine, lemon and 56,9% in guava juice. The proposed method is rapid and sensitive and can be used to analysis of organic acids in juice fruit samples.